2017
DOI: 10.1111/cas.13212
|View full text |Cite
|
Sign up to set email alerts
|

PVT1‐derived miR‐1207‐5p promotes breast cancer cell growth by targeting STAT6

Abstract: Accumulating evidence indicates that ectopic expression of non‐coding RNAs are responsible for breast cancer progression. Increased non‐coding RNA PVT1, the host gene of microRNA‐1207‐5p (miR‐1207‐5p), has been associated with breast cancer proliferation. However, how PVT1 functions in breast cancer is still not clear. In this study, we show a PVT1‐derived microRNA, miR‐1207‐5p, that promotes the proliferation of breast cancer cells by directly regulating STAT6. We first confirm the positive correlated expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…9 Moreover, a previous study showed that PVT1-derived miR-1207-5p contributed to breast cancer cells proliferation by negatively regulating STAT6 expression. 25 About 20% of human lncRNAs have been revealed to be physically associated with PRC2 complex, hinting the important roles of lncRNAs in recruiting polycomb-group proteins to their target genes. 26 Previous studies also showed that PVT1 could bind to EZH2, which modulated gene expression by promoting H3K27me3.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, a previous study showed that PVT1-derived miR-1207-5p contributed to breast cancer cells proliferation by negatively regulating STAT6 expression. 25 About 20% of human lncRNAs have been revealed to be physically associated with PRC2 complex, hinting the important roles of lncRNAs in recruiting polycomb-group proteins to their target genes. 26 Previous studies also showed that PVT1 could bind to EZH2, which modulated gene expression by promoting H3K27me3.…”
Section: Discussionmentioning
confidence: 99%
“…1F). Among them, miR-143-5p was reported to play an inhibitory role in gallbladder cancer (29), whereas miR-1207 promotes the progression of breast cancer (30). Besides, it has been indicated that miR-661 promotes the development of non-small cell lung cancer (31).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, studies on the mechanism of action of PVT1 in cancer have proliferated, and increasing evidence suggested that PVT1 could affect diverse biological behaviors of multiple tumors. Yan et al observed that the expression of PVT1 was positively associated to miR-1207-5p, which promoted the breast cancer cell proliferation by targeting STAT6 [43]. Ma et al revealed that PVT1 was highly expressed in glioma vascular endothelial cells, which increased the expression of Beclin1 and Atg7 by targeting miR-186, thereby promoting cell proliferation, migration and angiogenesis [44].…”
Section: Discussionmentioning
confidence: 99%